2014
DOI: 10.1071/mf13080
|View full text |Cite
|
Sign up to set email alerts
|

A long-term survey of Posidonia oceanica fish assemblages in a Mediterranean Marine Protected Area: emphasis on stability and no-take area effectiveness

Abstract: Marine reserves have become an important tool advocated to protect diversity, habitat or to restore depleted fish stocks. However, the links between reserve effect and temporal variability of assemblages remains equivocal. The present study presents the results obtained in a long-term series of annual surveys in the Scandola Marine Reserve (Corsica, North-western Mediterranean). An underwater visual census was performed on Posidonia oceanica seagrass beds. Species richness and density of target fish were posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…The taxa composition of the assemblages censused at the three locations investigated in Tunisia showed that fishes belonging to Sparidae, Labridae and Serranidae families were the most strongly represented in terms of number of species, a classic pattern for the western Mediterranean fish assemblage (e.g. García-Charton & Pérez-Ruzafa, 2001;Seytre & Francour, 2014). Fishes belonging to Sparidae and Labridae families were also the most strongly represented at the three studied locations in terms of both density (minimum 59% of total density) and biomass (minimum 71% of total biomass).…”
Section: Discussionmentioning
confidence: 99%
“…The taxa composition of the assemblages censused at the three locations investigated in Tunisia showed that fishes belonging to Sparidae, Labridae and Serranidae families were the most strongly represented in terms of number of species, a classic pattern for the western Mediterranean fish assemblage (e.g. García-Charton & Pérez-Ruzafa, 2001;Seytre & Francour, 2014). Fishes belonging to Sparidae and Labridae families were also the most strongly represented at the three studied locations in terms of both density (minimum 59% of total density) and biomass (minimum 71% of total biomass).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeable shifts in aquatic species composition (spatial distribution of species diversity and relative abundance) are more often than not associated with habitat loss (National Research Council 2001;Sainsbury et al 1997in Bianchi, 2000 and whilst effects can be felt from functional group removal, such as herbivorous groups in the Caribbean in the 1980s (Hughes, 1994) and extreme fishing pressure, e.g. sustained trawling or push nets, generally shifts in aquatic community assemblages are more likely through habitat and environmental change rather than through the targeting , or cessation of targeting, of certain species (Skilleter & Warren, 2000;Wilson et al, 2008;Seytre & Francour, 2013).…”
Section: Meeting Other Conservation Objectivesmentioning
confidence: 99%
“…Understanding the effects of fishing on aquatic species community composition is less developed despite the long history of fisheries management because of weak theoretical foundations and fluctuations in short-term assemblage, so long-term monitoring is required but often lacking (Seytre & Francour, 2013). This is especially the case for highly energetic environments such as mangroves and estuaries which may require more tailored monitoring to take account of the biophysical characteristics that distinguish these areas from each other, and therefore may need different management measures and regimes to achieve conservation objectives.…”
Section: Meeting Other Conservation Objectivesmentioning
confidence: 99%
“…Despite the pivotal role of seagrass, most tropical zone research and management still focuses on coral reefs [ 29 , 30 ]. So far, very few studies have investigated effects of MPAs on seagrass-associated fish, but these indicate that there are positive effects on fish density, size and biomass [ 28 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%